Analysis of Sociodemographic and Clinical Factors Associated with Hospitalized Stroke Patients of Bangladesh (Faridpur Medical College Journal, 2011)
A hospital based cross sectional study was carried out to analyze prevalence of risk factors for stroke in hospitalized patient in a medical college hospital. 100 patients were chosen using purposive sampling technique. Highest incidence of stroke was between the 6th and 7th decade. Patients came from both urban (54%) and rural (46%) areas and most of them belong to the low-income group (47%). In occupational category; service holder (28%) and retired person (21%) were the highest groups. Most of the study subjects were literate (63%). CT scan study revealed that the incidence of ischaemic stroke was 61% and haemorrhagic stroke 39%. Analysis indicated hypertension as major risk factor for stroke (63%) and major portion of the patients (42.85%) were on irregular or no treatment. Twenty four percent of the patients had heart diseases and out of 24 patients 45.83% were suffering from ischaemic heart disease. The present study detected diabetes in 21% patients. Fifty three percent of the study subjects were smoker, 39% patients had habit of betelnut chewing. Out of 26 female patients, only 23% had history of using oral contraceptives. Majority of the patients were sedentary workers (46%). Thirty seven percent of the stroke patients were obese. Among the stroke patients 9% had previous history of stroke and 3% had TIA respectively. Most of the patients (21%) were awake while they suffered from stroke and the time of occurrence was mostly in the afternoon (46%). This study found that hypertension, cigarette smoking, ischaemic heart disease and diabetes mellitus are the major risk factors prevalent in our community while other risk factors demand further study. Key words: stroke; risk factors; hospitalized patients; Bangladesh. DOI: 10.3329/fmcj.v6i1.7405 Faridpur Med. Coll. J. 2011;6(1): 19-23